2019
DOI: 10.1101/829622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple chromosomal inversions contribute to adaptive divergence of a dune sunflower ecotype

Abstract: Both models and case studies suggest that chromosomal inversions can facilitate adaptation and speciation in the presence of gene flow by suppressing recombination between locally adapted alleles. Until recently, however, it has been laborious and time-consuming to identify and genotype inversions in natural populations. Here we apply RAD sequencing data and newly developed population genomic approaches to identify putative inversions that differentiate a sand dune ecotype of the prairie sunflower ( Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 58 publications
(97 reference statements)
2
66
1
Order By: Relevance
“…(B) Inversions become established through a process similar to (A) but by carrying a combination of alleles at two loci that are adapted to different aspects of the local environment (triangles and squares in different colors). For example, in a dune ecotype of the prairie sunflower (Helianthus petiolaris), larger seed size and tolerance to low nutrient soils were found to map to the same inversions (Huang et al, 2019;Todesco et al, 2019). (C) Mixed geographic model proposed by Feder et al (2011).…”
Section: Origin and Establishment Of Inversionsmentioning
confidence: 98%
See 4 more Smart Citations
“…(B) Inversions become established through a process similar to (A) but by carrying a combination of alleles at two loci that are adapted to different aspects of the local environment (triangles and squares in different colors). For example, in a dune ecotype of the prairie sunflower (Helianthus petiolaris), larger seed size and tolerance to low nutrient soils were found to map to the same inversions (Huang et al, 2019;Todesco et al, 2019). (C) Mixed geographic model proposed by Feder et al (2011).…”
Section: Origin and Establishment Of Inversionsmentioning
confidence: 98%
“…Surprisingly, inversions segregating within species often have no visible effect on fertility, such as reported for Brassica oleracea (Kianian and Quiros, 1992) and maize (Fang et al, 2012). In Mimulus and Helianthus, crosses between ecotypes that are separated only by inversions do not show reduced pollen viability (Lowry and Willis, 2010;Ostevik et al, 2016;Huang et al, 2019), although meiotic abnormalities diagnostic for inversions have been reported for interspecific crosses (Chandler et al, 1986). This suggests that the reduction in recombination associated with inversions within plant species is typically achieved by disrupting pairing and crossing over between inverted regions (Searle, 1993) rather than selection against inviable recombinant gametes.…”
Section: Different Likelihood Of the Establishment Of Inversions And mentioning
confidence: 99%
See 3 more Smart Citations